Heavy Metal Identification in Water Resources and the Surrounding Environment of the Cirasea Riparian Zone, Indonesia - Maria, Rizka; Astuti, Ratna Dwi Puji; Rusydi, Anna Fadliah; Marganingrum, Dyah; Mulyono, Asep; Nurohman, Heri; Dida, Eki Naidania; Damayanti, Retno; Shoedarto, Riostantieka Mayandari; Rahayudin, Yudi; Taufiqurrahman, Adie; Ferdiano, Muhammad Rio; Nugraha, Detizca Melia (Indonesian Journal of Chemistry, 2024)
The Cirasea River can provide water for both the Bandung basin and agricultural irrigation. Intensive agriculture, industry, and land use changes could have an impact on water quality. The purpose of this study is to look at the origins of heavy metals in riparian water resources. Heavy metal analysis was performed on 13 groundwater and river water samples. Heavy metals in water sources were compared with sediment and soil. The samples were analyzed for heavy metals using an AAS instrument. The research method employs statistical, geographical, and heavy metal pollution index (HPI). The HPI for river water was 131, whereas groundwater was 93. River water with an HPI value of more than 100 is highly polluted, indicating that it is unsafe for human consumption and has negative health consequences. Data verification with heavy metals in sediments reveals the presence of heavy metals coming from geogenic circumstances in various locations in the upstream area. Heavy metals in downstream areas result from geological factors and anthropogenic activities in the surrounding area. The long-term effects of heavy metal pollution along the riparian zone will become apparent. More research is needed on communities that depend on groundwater supplies along the Cirasea watershed.